2019
DOI: 10.1002/hep.30604
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide Association Studies of Specific Antinuclear Autoantibody Subphenotypes in Primary Biliary Cholangitis

Abstract: Anti‐nuclear antibodies to speckled 100 kDa (sp100) and glycoprotein 210 (gp210) are specific serologic markers of primary biliary cholangitis (PBC) of uncertain/controversial clinical or prognostic significance. To study the genetic determinants associated with sp100 and gp210 autoantibody subphenotypes, we performed a genome‐wide association analysis of 930 PBC cases based on their autoantibody status, followed by a replication study in 1,252 PBC cases. We confirmed single‐nucleotide polymorphisms rs492899 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…Of note, a recent study performed a genome-wide association analysis of 930 PBC cases based on their autoantibody status and demonstrated a significant genetic predisposition to the sp100 autoantibody, but not the gp210 autoantibody, subphenotype in PBC patients. 96 These results confirm prior reports of distinct HLA associations for sp100 positive patients. Although additional studies will be necessary to determine if these findings have clinical significance to PBC pathogenesis, the striking difference in genetic predisposition observed between the two phenotypes may indicate distinct roles of these two autoantibodies in PBC.…”
Section: Genetics Of Pbcsupporting
confidence: 90%
“…Of note, a recent study performed a genome-wide association analysis of 930 PBC cases based on their autoantibody status and demonstrated a significant genetic predisposition to the sp100 autoantibody, but not the gp210 autoantibody, subphenotype in PBC patients. 96 These results confirm prior reports of distinct HLA associations for sp100 positive patients. Although additional studies will be necessary to determine if these findings have clinical significance to PBC pathogenesis, the striking difference in genetic predisposition observed between the two phenotypes may indicate distinct roles of these two autoantibodies in PBC.…”
Section: Genetics Of Pbcsupporting
confidence: 90%
“…We confirmed that the prevalence of anti‐Sp100 antibodies in PBC patients was within the previously reported ranges, 6‐15 but no significant difference in the frequency of anti‐Sp100 was not detected between the AMA‐positive and AMA‐negative PBC patients, indicating that anti‐Sp100 cannot become a complementary serological marker of PBC in AMA‐negative patients. Our analyses also did not elucidate that anti‐Sp100 was associated with the disease severity, which did not support the previous studies 5,11,18 …”
Section: Discussionsupporting
confidence: 89%
“…Several studies have indicated that autoantibodies of gp210 are strong predictors of PBC prognosis (54,55). In addition, faster disease progression, and significantly higher hepatic failure have been found in anti-gp210-positive patients (56,57). In this study, we have observed that the expression of galactose was increased in anti-gp210-positive patients with PBC.…”
Section: Discussionsupporting
confidence: 55%